The Effectiveness of Awareness-Based SBCC Through Parenting Patterns and Intensive Nutrition in Handling Stunting in Ropang Subdistrict - Ana Lestari; Luh Putu Sri Yuliastuti; Atri Wahyu Tarikawati (Biomedical Journal of Indonesia, 2026)
Introduction. Stunting is a public health indicator that reflects the quality of human resources and remains a significant challenge in various regions of Indonesia, including Ropang District, Sumbawa Regency. This study aims to evaluate the effectiveness of an awareness-based Social Behavioral Change Communication (SBCC) approach through improved parenting and intensive nutrition in efforts to address stunting. Methods. The study used a mixed-method design with a quasi-experimental pretest-posttest approach involving 12 mothers with stunted children. The intervention was conducted over two months through face-to-face education, printed and digital educational media, and a community-based approach. Quantitative data analysis used the Wilcoxon test and paired t-test, while qualitative data was obtained from in-depth interviews and field observations. Results. The results showed a significant increase in parenting patterns (p=0.046) and eating patterns (p=0.025), while the increase in nutritional knowledge was not significantly different (p=0.564). Anthropometrically, there were significant differences in height (p=0.014) and weight (p=0.037) between the pre- and post-intervention periods. Conclusion. This improvement indicates that changes in parenting behavior and feeding practices, delivered through the SBCC approach, contributed to improvements in children's nutritional status.